Study of the Osteoporotic Changes in Postmenopausal Women with Type-2 Diabetes Mellitus - Jahan, Ayesha; Begum, Rokeya; Shamsuddin, Khaled Bin (Bangladesh Journal of Nuclear Medicine, 2017)
Introduction: Osteoporosis and Diabetes Mellitus (DM) are common medical conditions in the society with an increasing prevalence in elderly people. Osteoporosis is more common in female than male and postmenopausal women are vulnerable to it. Objective: The aim of this study was to verify the effect of type-2 diabetes mellitus on bone mineral density in postmenopausal women and, thereby, to evaluate the risk of osteoporosis in them. Materials and Methods: This cross-sectional study was carried out at National institute of Nuclear Medicine and Allied Sciences (NINMAS), BSMMU campus, Shahbagh, Dhaka, over a period of one year. 175 postmenopausal women were enrolled as study subjects, among them 72 (41.10%) were diabetic and rest 103 (59.90%) were nondiabetic and they were assigned as Group-I and Group-II respectively. The bone mineral density (BMD) was measured by central DEXA device at lumbar spines and left femoral neck of each study subject. Results: The mean (±SD) ages of group-I and group-II were 58.79 (±8.06) and 58.27 (±8.39) respectively with an age range of 45 to 75 years in both cases. A total of 30 (41.66%) patients in diabetic group (group-I) and 40 (38.83%) patients in non-diabetic (group-II) had osteoporosis at lumbar spines. On the other hand, 40 (56.94%) patients in group-I and 58 (56.31%) patients in group-II had osteoporosis at femoral neck. The Odds Ratios of osteoporosis for lumbar spines and femoral. neck were 1.125 and 1.026 respectively. The differences of frequencies of osteoporosis between group-I and group-II were not statistically significant at any anatomical site and the association between osteoporosis and type-2 diabetes mellitus was not significant. According to Odds Ratio type-2 diabetes mellitus was not a risk factor for developing osteoporosis in postmenopausal women. Conclusion: Postmenopausal women are prone to develop osteoporosis and type-2 diabetes mellitus may have adverse influence on osteoporosis, which was supported by few previous studies. This study could not establish any significant effect of type-2 diabetes mellitus on osteoporosis in postmenopausal women. Bangladesh J. Nuclear Med. 18(1): 21-26, January 2015